The Contribution of 3D models to serious games applications - Κοντογιάννη, Γεωργία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2015)
Digital technologies have affected many fields of computer graphics such as Games and especially the Serious Games field. This kind of games is usually used for educational proposes in many scientific fields such as Health Care, Military, Education etc. Digital Cultural Heritage is a scientific field in which Serious Games are gradually applied and many applications have been developed according to the literature. Realistic 3D models which have been produced using different photogrammetric methods could be a useful tool for the creation of Serious Games applications in order to make the final result more realistic and closer to the reality. The basic goal of this thesis is the development of a Serious Game for the Ancient Agora of Athens by using different kind of 3D documentation data created in previous projects. These models vary not only as far as their production methods (Time of Flight Laser scanner, Structure from Motion, Virtual Historical reconstruction etc.) is concerned, but also as far as their era, because some of them are illustrated according the existing situation and some others according to how these monuments would have looked like in the past. The Unity 3D Game development engine was used for the game development in which all these models were inserted in the same file format. The scenario of the game includes two virtual tours of the area in different eras and a quiz game. In this quiz game question are posed to the user for each monument with three possible answers of which the player should select the correct one. In case that the answer is right he will continue with the next question. In case that the answer is wrong the player will be presented with the correct answer and an explanation about his mistake. Furthermore a preliminary stage about ancient Greek temples and their orders is created in order to help the players to acquire more knowledge and facts about Ancient Greek architecture. The evaluation of the game was carried out by a group of people, experienced and non-experienced in Cultural Heritage field, who played and evaluated the game by filling in a carefully prepared online questionnaire. The game was improved according these evaluations for a better result. Finally some concluding remarks and the future evolution of this game is presented.